Menthol Flavor in E-Cigarette Vapor Modulates Social Behavior Correlated With Central and Peripheral Changes of Immunometabolic Signalings - Xu, Zhibin; Tian, Ye; Li, A.-Xiang; Tang, Jiahang; Jing, Xiao-Yuan; Deng, Chunshan; Mo, Zhizhun; Wang, Jiaxuan; Lai, Juan; Liu, Xuemei; Guo, Xuantong; Li, Tao; et al. (Frontiers in Molecular Neuroscience, 2022)
The use of electronic cigarette (e-cigarette) is increasing dramatically worldwide. More than 8,000 flavors of e-cigarette are currently marketed and menthol is one of the most popular flavor additives in the electronic nicotine delivery systems (ENDS). There is controversy over the roles of e-cigarettes in social behavior and little is known about the potential impacts of flavorings in the ENDS. We here aimed to investigate the effects of menthol flavor in ENDS on social behaviors in long-term vapor exposed mice with daily intake limit, and the underlying immunometabolic changes in the central and peripheral systems. We found that, the addition of menthol flavor in nicotine vapor enhanced the social activity compared with nicotine alone. The dramatic reduced activation of cellular energy measured by AMPK signaling in the hippocampus were observed after chronic exposure of menthol-flavored ENDS. Multiple sera cytokines including C5, TIMP-1 and CXCL13 were decreased accordingly as the peripheral immunometabolic responses to menthol flavor in nicotine vapor. The serum level of C5 was positively correlated with the activity alteration of the AMPK-ERK signaling in the hippocampus. Our current findings provide evidence of the enhancement of menthol flavor in ENDS on social functioning, which are correlated with the central and peripheral immunometabolic disruptions, thus raises the vigilance of the cautious addition of various flavorings in e-cigarettes and the urgency of further investigations on the complex interplay and health effects of flavoring additives with nicotine in e-cigarettes.